Climate-Smart Technologies for Sustainable Farming (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The growing frequency and intensity of weather change-induced occasions pose unparalleled demanding situations to global agriculture, threatening meals safety and livelihoods. In reaction to this, the adoption of ClimateSmart Technologies (CSTs) has emerged as a pivotal method to support farming practices in opposition to the impacts of weather change even as fostering sustainability. This complete review explores the diverse landscape of CSTs, their packages across diverse farming systems, and their multifaceted impacts on resilience, mitigation, and sustainability. The paper begins by using elucidating the huge spectrum of CSTs, categorizing them into adaptation technologies that decorate resilience, mitigation technology that reduce emissions, and sustainable intensification technology that sell productiveness even as minimizing environmental footprints. The subsequent sections delve into precise packages of CSTs, spanning crop control, livestock technology, water control, and the innovative realm of virtual agriculture. From precision farming and drought-resistant plants to IoT-enabled precision agriculture, these technologies exhibit a promising trajectory in the direction of climate-smart and sustainable farming.An in-depth evaluation of the effect of CSTs follows, highlighting their function in bolstering the resilience of agricultural structures and mitigating greenhouse gasoline emissions. The economic, social, and environmental implications of CST adoption are scrutinized, shedding light on the transformative potential of those technology to reshape the agricultural landscape. Case research from diverse areas offer concrete examples of successful CST implementation, illustrating the tangible advantages experienced by using farming groups.However, challenges within the enormous adoption of CSTs persist. Economic limitations, knowledge gaps, and social dynamics pose hurdles that need addressing. The paper concludes via emphasizing the pressing want to conquer these challenges, advocating for endured research and innovation. As agriculture stands at the frontline of climate exchange affects, embracing and scaling up the adoption of weather-clever technology isn't always only a desire however a need for building a resilient and sustainable future for international agriculture.